Mediating Role of Psychological Capital in the Relationship Between Social Support and Self-Neglect Among Chinese Community-Dwelling Older Adults - Zhao, Binyu; Wang, Hangsai; Xie, Chunqi; Huang, Xianhong; Cao, Meijuan (Frontiers in Psychology, 2022)
Objectives: Self-neglect in older adults has become an important public health issue and is associated with negative health outcomes and increased morbidity and mortality. Social support has been recognized as a prominent predictor of self-neglect, but the underlying mechanism is unclear. This study aims to investigate and illustrate the associations among social support, psychological capital, and self-neglect. Methods: This study used a cross-sectional convenience sampling design. A total of 511 older adults were recruited in Chinese communities. Spearman’s correlation coefficient and hierarchical multiple regression analysis were performed to assess the influencing factors of self-neglect. A structural equation model was applied to test the hypothesized mediation model. Results: Social support and psychological capital were found to be negatively related to self-neglect. Social support and psychological capital explained 5.0% and 12.1% of the incremental variances of older adults’ self-neglect, respectively. Psychological capital acts as a mediator between social support and self-neglect. Conclusions: Self-neglect among older adults is a rising problem in China. Social support and higher psychological capital could decrease the risk of self-neglect in older adults. It is crucial to improve social networks and facilitate psychological interventions to reduce such self-neglect.